Controlling Differential Motor Using Microcontroller - Mat Jemin, Mohammad Azreen (Universiti Sains Malaysia, 2018)
In robotic system that using motor as a prime mover, speed control is one of the crucial element in controlling the robot. The control component will provide a steady velocity to the system and adjust the speed of the robot's movement according to a desirable velocity condition. The main target in this project is to design a speed controlling system for mobile robot. It is a key aspect that plays a role in driving robot movements in accordance with the co-ordinated instructions that are programmed into a robotic system. Some processes need to be pursued in order to achieve this objective, including designing a speed controller using PID controller based on some classical methods, analyzing and comparing performance obtained from different methods and selecting the best classical method and suitable tuning method. The most complex part in designing the speed controller is to determine the appropriate and stable PID parameters according to the desired characteristics. Final results can be achieved by analyzing the results obtained from all the methods used. PID controller for controlling the velocity of brushed DC motor successfully designed.